PENGARUH AUDIT INTERNAL, KOMPETENSI AUDITOR, KESESUAIAN KOMPENSASI DAN WHISTLEBLOWING SYSTEM TERHADAP PENCEGAHAN FRAUD - Muhammad Rahmat; Defri; M. Abdul Kholik; Silvia Rizli Basnawati; Mefri Yudi Wisra (Postgraduate Management Journal, 2023)
Fraud or commonly known as fraudulent activities carried out in various modes and continues to increase over time. The high number of fraud cases that occur in Indonesia must be taken very seriously, for example by forming an internal audit team that has a really valuable role in monitoring activities to determine whether programs and fraud prevention have been running effectively. This study plans to decide the impact of internal audit, auditor competence, compensation suitability and whistleblowing system on fraud prevention in the Inspectorate General of the Ministry of Maritime Affairs and Fisheries with a sample of 117 respondents. Data collected through questionnaires, the method used in this study is multiple linear regression. The results show that internal audit, auditor competence, compensation suitability and whistleblowing system have a significant effect on fraud prevention